The Effect of Market Orientation, Marketing Innovation on Competitive Advantage and Business Performance: An Empirical Study in Micro Business of Batik Jambi - Endah Lestari, Savitri; Hidayat, Kadarisman; Abdillah, Yusri (Profit: Jurnal Adminsitrasi Bisnis, 2023)
This research aims to examine the effect of Market Orientation (MO), Marketing Innovation (MI) on the Competitive Advantage (CA) and Business Performance (BP) of the Batik Jambi industry during covid 19 pandemic in 2020. This research helps the Micro Business of Batik Jambi Industry to apply the results of this research in increasing competitive advantage and business performance in all market conditions. The research method used is quantitative. This research was conducted in the Micro Business of Batik Jambi Industry, Seberang Jambi City, with a research sample of 33 Micro Business owners with a nonprobability sampling technique with a census sampling approach (saturated). The data were analyzed using PLS (Partial Least Square). The results showed that of the six hypotheses proposed, two hypotheses had an insignificant effect; namely, Market Orientation has no significant effect on Competitive Advantage and Business Performance. Meanwhile, the other four hypotheses significantly affect the dependent variable in this research, which means that MO has helped increase the MI of the Batik Jambi Industry. MI has also helped increase CA and BP during and after the covid-19 pandemic. CA in the Micro Business of Batik Jambi Industry has been implemented in stages and can improve BP's business.